Experience With the Pipeline Embolization Device for Posterior Circulations Aneurysms: A Multicenter Cohort Study. (18th December 2021) - Griessenauer, Christoph J; Enriquez-Marulanda, Alejandro; Taussky, Philipp; Biswas, Arundhati; Grandhi, Ramesh; Xiang, Sissi; Hong, Tao; Rinaldo, Lorenzo; Lanzino, Giuseppe; Brinjikji, Waleed; Burkhardt, Jan-Karl; Kan, Peter; et al.
Graphical Abstract: